Electrolytic changes in dogs with infectious Gastroenteritis - Guaman-Simba, Dorys Daniela; Castillo-Hidalgo, Edy Paul; Armas-Ariza, Juan Carlos (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The aim of this research was to analyze the electrolyte profile: Na (µMol·L-1), K (µMol·L-1), Cl (µMol·L-1), presented in animals, namely dogs with viral and parasitic gastroenteritis. In this regard, 30 male and female patients (n=30) of distinct range of ages, from the Municipal shelter of Ambato-Ecuador were treated and tested. These animals presented gastrointestinal symptoms; therefore, a detailed clinical history was taken. Thereafter, 2 mililiter (mL) of blood was taken from the puncture of the jugular vein in order to conduct an electrolyte analysis. These analyses were processed and conducted in a DRI-CHEM NX500i machine, made by the Japanese brand Fujifilm in 2016. Additionally, Canine Parvovirus Test kits, specifically (SensPERT) were used. Furthermore, stool samples were taken in order to conduct a coprological examination. The result of this investigation show cases that the K values in diarrhea caused by parasites were higher than those presented in cases where diarrhea those that showed the highest prevalence were Toxocara canis and Canine Parvovirus type 2 (CPV-2). El objetivo del presente trabajo de investigación fue establecer el perfil electrolítico: Na (micromol·litros-1) [µMol·L-1], K (µMol·L-1), Cl (µMol·L-1), en perros con gastroenteritis viral y parasitaria, para lo cual se analizaron 30 pacientes (n=30) de todas las edades y sin diferencia de sexo, procedentes del albergue municipal de Ambato, Ecuador, los cuales presentaron síntomas gastrointestinales, a estos pacientes se levantó la Historia Clínica detallada, posterior a ello se tomaron 2 mililitros (mL) de sangre por punción de la vena yugular, para análisis de electrolitos, las muestras de sangre obtenidas fueron procesadas en un equipo DRI-CHEM NX500i, año 2016, de marca Fujifilm; de fabricación japonesa; de igual forma se realizó el Test Kit de Canine Parvovirus (SensPERT) y se recolectaron muestras de heces para examen coprológico. Los valores de K en diarreas producidas por parásitos se mostraron superiores frente a las ...